Characteristic of Perineural Invasion in Hilar Cholangiocarcinoma Based on Whole-Mount Histologic Large Sections of Liver - Wang, Si-Yuan; Jiang, Nan; Zeng, Jian-Ping; Yu, Shao-Qing; Xiao, Ying; Jin, Shuo (Frontiers in Oncology, 2022)
Background & Objective. Perineural invasion is an important biological feature of hilar cholangiocarcinoma (HCCA). We developed a whole-mount, digital, panoramic pathological system of the liver to evaluate peripheral nerve invasion (PNI) of HCCA. Methods. Using sampling, fixation, dehydration, embedding, sectioning, H&E and immunohistochemical (IHC) staining, and scanning, the characteristics of intrahepatic and extrahepatic PNI in 20 patients with Bismuth type III and type IV HCCA were analyzed with the whole-mount pathological system. Correlation between the characteristics of nerve invasion and tumor size, vascular invasion (artery, portal vein), degree of differentiation, MVI, CA-199, and differentiation degree of HCCA was statistically evaluated. Results. The panoramic digital pathological system of the liver was successfully established, which enabled us to observe intrahepatic and extrahepatic distribution of HCCA and whether surrounding tissues including nervous, blood, and lymph vessels were infiltrated. Extrahepatic and intrahepatic PNI were identified in 20 (100%) patients and 1 (5.0%) patient, respectively. Vessel density decreased in most invaded nerves presented by CD-34, which correlated with 100% of poorly differentiated and 83% of moderately differentiated tumors (P<0.008). Conclusion. This study established a panoramic pathological system of the liver that can be used for clinical diagnosis and research, and confirmed that extrahepatic PNI is prevalent, but intrahepatic nerve invasion is rare and does not accompany the invasion scope of bile ducts in types III and IV HCCA. In addition, moderately and poorly differentiated malignant tumors are more prone to PNI, independent of blood supply